A phytosociological study of a lowland forest at the Tesso Nilo National Park, Riau. - Purwaningsih Purwaningsih; Kuswata Kartawinata (Indonesian Journal of Applied Environmental Studies, 2022)
A  phytosociological study of a lowland forest was carried out at the Tesso Nilo National Park (TNNP), Riau. The objective of the study was to obtain quantitative data on the floristic composition and structure of the above-mentioned lowland forest. By establishing a plot of 1.0 ha, the quadrat method was used to collect the data. We recorded a total of 1,303 individuals of trees and saplings with diameters ≥ 2 cm, comprising 304 species, 153 genera, and 62 families. Using the dominance and density of two tree species, the forest community in the plot can be designated as Sloetia elongata-Pimelodendron griffithianum Association. The species sharing the dominance were Sloetia elongata (Importance Value, IV = 14.43), Pimelodendron griffithianum (IV = 6.17), Santiria laevigata (IV = 5.45) and Xylopia caudata (IV = 5.17). Diameter records showed that 80% of trees in the plot were dominated by small individuals with diameters between 10-30 cm. Trees with diameters 30 cm were Dracaena cf. porteri (diam. 75.6 cm), Artocarpus elasticus (63.3 cm), and Ctenolophon parviflorus (62.1 cm).  Dipterocarp species was not important since they contributed only 4%, while non-dipterocarps shared 96% comprising 61 families. The highest basal area was shared by nine species, including one dipterocarp, Shorea leprosula. Several dipterocarp species occurring in TNNP have been listed in the IUCN Red List of Threatened Species, including Anisoptera megistocarpa, Hopea ferruginea, Hopea pachycarpa, Shorea atrinervosa, Shorea faguetiana,   Shorea lepidota and Vatica gamosepala. The presence of a large number of small trees and a few large trees indicated that the forest in the plot was regenerating after heavy disturbances. Regenerating species were divided into five categories, in which 13 species were regenerating well with Sloetia elongata being the best regenerating species while dipterocarps were represented by Shorea acuminata. The occurrence of the majority of trees with a height of 20 m further confirmed the dynamic status of the forest. The importance of primary and secondary forests in TNNP was discussed. Restoration to the original forest was recommended by planting primary forest species, including endemic, rare, and endangered tree species.